2009
DOI: 10.1111/j.1467-9221.2009.00735.x
|View full text |Cite
|
Sign up to set email alerts
|

Information Distortion and Voting Choices: The Origins and Effects of Factual Beliefs in Initiative Elections

Abstract: To account for voter decision making in initiative elections, we integrate theory and research on public opinion, misinformation, and motivated reasoning. Heuristic and motivated reasoning literatures suggest that voters' preexisting values interact with political sophistication such that politically knowledgeable voters develop systematically distorted empirical beliefs relevant to the initiatives on their ballots. These beliefs, in turn, can predict voting preferences even after controlling for underlying va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 27 publications
(47 reference statements)
0
29
0
1
Order By: Relevance
“…4 Like Wells et al (2009), we therefore expect that information concerning one's beliefs about controversial empirical questions in politics (i.e. factual beliefs) will be processed like information concerning one's political views (i.e.…”
Section: Theoretical Expectationsmentioning
confidence: 99%
“…4 Like Wells et al (2009), we therefore expect that information concerning one's beliefs about controversial empirical questions in politics (i.e. factual beliefs) will be processed like information concerning one's political views (i.e.…”
Section: Theoretical Expectationsmentioning
confidence: 99%
“…Without that knowledge, one does not know where to turn for reliable cues. Following this view, we posited (Wells et al., ) that values play a role in distorting individuals’ empirical beliefs only when they have sufficient political knowledge to connect underlying values with the issue at hand.…”
Section: A Theoretical Model Of Distorted Empirical Beliefsmentioning
confidence: 99%
“…Though we know that distorted beliefs can have political implications, we know relatively little about how misperceptions form and the conditions under which they become politically consequential. The present study aims to advance our understanding of the role of factual beliefs in opinion formation and expression by refining a model introduced in Wells et al (2009), which elaborated previously unacknowledged implications of Zaller's (1992) theory of how empirical political beliefs can shape opinions.…”
mentioning
confidence: 98%
“…In the case of election administrators, one might anticipate that those individuals who are motivated to throw a ballot away might ''confirm'' characteristics of the ballot that would make the ballot be discountedand this may be the case even when ballot counters are well-trained and highly driven by accuracy motives. Indeed, Wells et al (2009) found that certain political beliefs are influenced by political values, particularly in cases where individuals are politically sophisticated. ''Disconfirmation bias,'' in a similar vein, occurs when people cannot discount their original beliefs when evaluating policies.…”
Section: Motivated Reasoningmentioning
confidence: 99%